DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN KONSUMEN PRIMER - Rida Anisa Permata (2021)
This study was conducted to find out if there is an influence between financial performance measured using return on asset, firm size measured using natural logarithms (LN) total assets and capital structure measured using debt to equity ratio to firm value that use proxy price to book value in primary consumer goods companies. The research population amounted to 92 companies listed on the Indonesia Stock Exchange in the primary consumer goods industry sector, namely the period 2016-2020. Furthermore in this study, as many as 58 companies were useful as samples with sampling techniques, namely purposive sampling methods. This type of research is quantitative research using the help of E-Views 12 and Microsoft Excel 2010 software programs and the application of a significance level of 5% (0.05). From the results of hypothesis tests as well as analysis using the Data Panel Regression Analysis technique, it was found that financial performance expressed a positive and significant effect on firm value, firm size had a negative and significant effect on firm value, and the capital structure had a positive and significant effect on firm value.